Choosing the most suitable sustainability report standard for banking industry: A case study of Bank ABC - Chintia Rudiyanto; Oktofa Yudha Sudrajad (Journal of Digital Business and Marketing, 2025)
Purpose: This study aims to evaluate and prioritize sustainability reporting standards in the banking sector by identifying key criteria influencing their selection, with a particular focus on integrating local regulatory compliance and global best practices. Research Methodology: The research employs a mixed-methods approach, beginning with qualitative interviews with key stakeholders and a literature review to identify relevant criteria. Insights from this phase inform the quantitative analysis using the Analytic Hierarchy Process (AHP). Five sustainability reporting experts from ABC Bank served as respondents, assessing alternative standards based on predetermined criteria derived from both interviews and literature studies. Results: The findings indicate that “integration with financial metrics” and “use of technology” are the most critical criteria in selecting sustainability reporting standards. AHP analysis shows that while POJK 51 meets regulatory requirements, global frameworks such as GRI and SASB offer broader and more investor-oriented disclosures. Combining multiple standards provides a more comprehensive approach, though it demands greater resources and capacity. Conclusion: The study concludes that hybrid adoption of local and global sustainability frameworks enhances reporting credibility, aligns with stakeholder expectations, and strengthens competitive positioning Limitations: The small sample size of five experts from a single bank limits the generalizability of findings. Contribution: This research provides empirical insights into the prioritization of sustainability reporting standards, offering practical guidance for banks and policymakers seeking to enhance ESG transparency and alignment with both domestic regulations and international standards.